(untitled) (Journal of Contemporary Dental Sciences, 2026)
In an era where scientific credibility directly influences clinical decision-making and public trust, maintaining high standards of ethical publishing is essential for the advancement of dental science. The Journal of Contemporary Dental Sciences (JCDS) is committed to fostering a culture of responsible scholarship through rigorous authorship criteria, double-blind peer review, plagiarism detection, prevention of duplicate publication, and transparent disclosure of conflicts of interest. Adhering to internationally recognized guidelines such as those of the ICMJE and COPE, JCDS ensures that contributions reflect genuine intellectual involvement and accountability. The journal embraces responsible integration of emerging technologies, including artificial intelligence tools, while emphasizing human oversight and full disclosure to safeguard research integrity. As an open-access publication under the Creative Commons Attribution License, JCDS enhances accessibility, equity, and knowledge dissemination. Integration with Crossref and DOI registration ensures persistent article identification, reliable citation linking, and increased global visibility. Through collaboration with BanglaJOL, INASP, Ubiquity Press, and Crossref, JCDS strengthens editorial governance and aligns itself with international publishing standards. By promoting transparency, accountability, and ethical rigor, the journal contributes to the development of a robust research culture in Bangladesh and positions itself as a trusted platform for high-quality dental scholarship in the global academic community. J. Contemp. Dent. Sci. 2026;14(1):1–2